Neofunctionalization of an ancient domain allows parasites to avoid intraspecific competition by manipulating host behaviour. - Chen, J.; Fang, G.; Pang, L.; Sheng, Y.; Zhang, Q.; Zhou, Y.; Zhou, S.; Lu, Y.; Liu, Z.; Zhang, Y.; Li, G.; Shi, M.; et al. (Nature communications, 2021)
Intraspecific competition is a major force in mediating population dynamics, fuelling adaptation, and potentially leading to evolutionary diversification. Among the evolutionary arms races between parasites, one of the most fundamental and intriguing behavioural adaptations and counter-adaptations are superparasitism and superparasitism avoidance. However, the underlying mechanisms and ecological contexts of these phenomena remain underexplored. Here, we apply the Drosophila parasite Leptopilina boulardi as a study system and find that this solitary endoparasitic wasp provokes a host escape response for superparasitism avoidance. We combine multi-omics and in vivo functional studies to characterize a small set of RhoGAP domain-containing genes that mediate the parasite's manipulation of host escape behaviour by inducing reactive oxygen species in the host central nervous system. We further uncover an evolutionary scenario in which neofunctionalization and specialization gave rise to the novel role of RhoGAP domain in avoiding superparasitism, with an ancestral origin prior to the divergence between Leptopilina specialist and generalist species. Our study suggests that superparasitism avoidance is adaptive for a parasite and adds to our understanding of how the molecular manipulation of host behaviour has evolved in this system.